2009
DOI: 10.1080/17470210802633461
|View full text |Cite
|
Sign up to set email alerts
|

Further analyses of the effects of practice, dropout, sex, socio-economic advantage, and recruitment cohort differences during the University of Manchester longitudinal study of cognitive change in old age

Abstract: A sample of 4,314 volunteers who, when first recruited, were aged from 41 to 93 years were quadrennially tested from 2 to 4 occasions during the next 4 to 20 years on the Cattell Culture Fair intelligence test, 2 tests of information-processing speed, the Wechsler Adult Intelligence Scale (WAIS) vocabulary test, and 3 memory tests. After significant effects of practice, sex, demographics, socio-economic advantage, and recruitment cohort had been identified and considered, performance on all tests declined with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
1
11
0
1
Order By: Relevance
“…Thus, unlike other studies that may focus attention on cognitive processes and disorders of aging, the original CHS sample was selected without regard for cognitive health – and this was not a factor in the recruitment process. However, the CHS-CS, like other longitudinal studies of normal aging, has the disadvantage of a survival bias, as the mean age of the participants is nearly 80 years (Euser et al, 2008; Rabbitt et al, 2008; Rabbitt et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Thus, unlike other studies that may focus attention on cognitive processes and disorders of aging, the original CHS sample was selected without regard for cognitive health – and this was not a factor in the recruitment process. However, the CHS-CS, like other longitudinal studies of normal aging, has the disadvantage of a survival bias, as the mean age of the participants is nearly 80 years (Euser et al, 2008; Rabbitt et al, 2008; Rabbitt et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Scoring was done in accordance with Cattell's (1987) instructions -one point was given for each correct answer on the test. The CFT is still being used fairly recently by other researchers (Rabbit, Lunn, Ibrahim and McInnes, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…The average ACE-R total score for the controls was 83.63 ± 7.90. 15 Because demographic variables such as education, age, sex, and cultural background may significantly influence cognitive performance, 16,17 our previous study also revealed an influence of age and schooling on Brazilian ACE-R scores. 15 21 using the Spanishlanguage version, divided controls into <14 and Z14 years of schooling, and found mean total scores of 79.93 (standard deviation [SD] = 7.64) and 86.37 (SD = 5.83), respectively.…”
mentioning
confidence: 94%